Bacterial diseases in the Philippines an annotated bibliography - Dugenia, Theresa P.; Rosal, Rosvida R.; Salazar, Nelia P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1982)
This bibliography is designed to meet the growing demands for literature of practical use in the medical and health professions in the Philippines.
The articles contained in this compilation, totaling 1,062, are those which deal with bacterial diseases in the Philippines. It covers the period from 1902 to 1981. Author and Subject indices are provided for ready reference.
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Bacterial diseases--Philippines--Bibliography.